2004
DOI: 10.1002/da.10144
|View full text |Cite
|
Sign up to set email alerts
|

Slow right perfrontal transcranial magnetic stimulation as a reatment for medication-resistant depression: A double-blind, placebo-controlled study

Abstract: Over the past decade, efforts have been made to assess the positive therapeutic effects of transcranial magnetic stimulation (TMS) by altering the excitability of the brain. We conducted a double-blind, placebo-controlled study to assess the efficacy of right prefrontal slow repetitive TMS in patients with treatment refractory major depression. This pilot study supports the therapeutic potential of rTMS in the low-frequency range of 1 Hz on right prefrontal cortex for the treatment of refractory major depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 20 publications
0
54
0
3
Order By: Relevance
“…Of the 10 RCTs on LF-rTMS for MD included in the previous meta-analyses, sixwere selected for the present investigation (Fitzgerald et al, 2003;Hoppner et al, 2003;Januel et al, 2006;Kauffmann et al, 2004;Klein et al, 1999;Stern et al, 2007). Also, we retrieved four RCTs on LF-rTMS for MD from MEDLINE, PsycINFO, EMBASE, CENTRAL, SCOPUS, and PQDT.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10 RCTs on LF-rTMS for MD included in the previous meta-analyses, sixwere selected for the present investigation (Fitzgerald et al, 2003;Hoppner et al, 2003;Januel et al, 2006;Kauffmann et al, 2004;Klein et al, 1999;Stern et al, 2007). Also, we retrieved four RCTs on LF-rTMS for MD from MEDLINE, PsycINFO, EMBASE, CENTRAL, SCOPUS, and PQDT.…”
Section: Literature Searchmentioning
confidence: 99%
“…However, questions remain as to whether this neuromodulation technique has clinically relevant effects in MD as RCTs to date have produced conflicting results. For example, Hoppner et al (2003) and Kauffmann et al (2004) showed that LF-rTMS was not superior to sham rTMS, whereas Stern et al (2007) and Pallanti et al (2010) found that LF-rTMS was associated with significantly higher rates of clinical improvement when compared with sham rTMS. A likely reason for these discrepant findings might be the lack of statistical power among some of the individual RCTs (Maxwell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Одна-ко результаты проведенных двойных слепых плацебо-контролируемых исследований оказались противоречи-выми. В одних исследованиях была показана эффектив-ность этого протокола, другие не продемонстрировали достоверных различий по сравнению с имитацией стиму-ляции [151][152][153][154]. Причиной могла служить различная мощность проведенных исследований [155].…”
Section: депрессияunclassified
“…Regarding left vs. right stimulation, the accumulated evidence favors the former as more studies were performed stimulating the left DLP-FC 74 ; and the evidence for low-frequency right DLPFC is mixed [75][76][77] . However, low-frequency rTMS seems to be better tolerated 78 and might be an interesting approach in selected cases.…”
Section: Parameters Of Stimulationmentioning
confidence: 99%